3-Phase Induction Motor Drive with PWM Modulator Using a 8-Bit Low Cost Micrcontroller - Küçükgüzel, E.; Bilgiç, Mehmet Oruç (My University, 2004)
This paper describes a study on a well studied subject, driving 3-phase induction motor. But the hardware used for the study is different than the conventional 16-bit microcontrollers or DSPs. The aim of the project is to lower the price of control hardware and achieve a satisfying performance with less expensive 8-bit microcontrollers.
Keywords: Induction Motor; PWM; Microcontroller